Preparation of Al4SiC4 with higher aspect ratio by a novel two-step method. Issue 16 (15th August 2022) - Zhao, Chunyang; Chen, Guangyao; Guo, Chunyu; Yang, Tao; Wang, Enhui; Hou, Xinmei
Abstract: Based on excellent comprehensive properties, aluminum silicon carbide (Al4 SiC4 ) becomes a promising candidate as antioxidant for MgO–C refractories. However, its addition tends to reduce the densification of corresponding refractories due to the plate structure with low aspect ratio, which aggravates the slag corrosion and oxidation during the practical application. Increasing the aspect ratio of Al4 SiC4 grains is a feasible approach to fabricate dense Al4 SiC4 -containing refractories. In this work, a strategy to fabricate Al4 SiC4 grains with higher aspect ratio based on a novel two-step solid reaction method was proposed. Firstly, Al4 SiC4 seeds was synthesized using Al4 C3 and SiC as raw materials at 1700 °C for 6 h. Secondly, the mixture of Al4 C3 and SiC with Al4 SiC4 seeds added was resintered. The aspect ratio of final Al4 SiC4 grains reaches up to 0.44 with the added proportion to be 50%. The growth mechanism follows the Ostwald ripening principle. This work can lay a good foundation for the practical application of Al4 SiC4 .